2014 6th International Symposium on Communications, Control and Signal Processing (ISCCSP) 2014
DOI: 10.1109/isccsp.2014.6877828
|View full text |Cite
|
Sign up to set email alerts
|

A new signal model for MIMO communication with compact parasitic arrays

Abstract: Significant research effort has been drawn over the last few years to reduce the hardware complexity and size of Multiple Input -Multiple Output (MIMO) systems and to push this promising technology even to lightweight and small portable devices. Among other architectures, single-fed MIMO systems with compact parasitic arrays are a possible candidate toward this goal. To facilitate the study and design of parasitic arrays for MIMO applications, this paper presents an alternative signal model considering the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The relation between the currents and voltages associated with the antenna elements of this array is given by the generalized Ohm's law [10]:…”
Section: Robust Arbitrary Precoding Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The relation between the currents and voltages associated with the antenna elements of this array is given by the generalized Ohm's law [10]:…”
Section: Robust Arbitrary Precoding Techniquementioning
confidence: 99%
“…The system model of a (M, (K, 1)) MU-MIMO setup formed between a BS with M transmit antennas and K single-antenna user terminals (UT) is given from an antenna perspective by [10] y = Hi + n,…”
Section: Robust Arbitrary Precoding Techniquementioning
confidence: 99%
“…3. The mutual information of PMH in a multiple-access iid Gaussian channel for different number of antenna elements at the UEs [9].…”
Section: ) Lmasmentioning
confidence: 99%
“…In order to perform closed-loop MIMO transmission using single-RF ESPAR antennas, we map the precoded symbols on the antenna currents [9]. Unfortunately, for some input signal constellations the required loading values may lead to circuit instability.…”
Section: Transmission Techniques 1) Arbitrary Channel-dependent Prmentioning
confidence: 99%
“…However, specific precoding scheme analysis is not included. An important result is reported in [25], where a new signal model is introduced for ESPARs and it is shown that the currents at the ports of the transmitting array can be considered as the input to the system. In [26], MIMO transmission with ESPARs is studied, where the convex optimization approach is employed to obtain the load values that satisfy the input impedance constraint for the ESPAR array.…”
Section: Introductionmentioning
confidence: 99%